Carl Schmitt between Science and Prophecy - Dobeš, Jan (Dějiny – teorie – kritika, 2009)
This article sets out the fundamental intellectual starting points of Carl Schmitt. It is concerned chiefly with his conception of law, the main features of his political philosophy, and his attitude to liberalism, parliamentarism, democracy, and the Nazi dictatorship. It also takes into account the way in which he used historical arguments to support his ideas. Particular attention is paid to the concept of the political, which Schmitt considered an independent sphere of human existence, one based on differentiating between friend and foe, an act performed by the wielder of sovereign political power. It is precisely the question of power and, linked to it, sovereign decision, which form the core of politics. Ethical or economic criteria must not enter this sphere. The natural framework in which the political is applied is the State, which appears outwardly in the sphere of foreign policy. In domestic policy the State is based on the identity of the ruler(s) and the ruled. In the twentieth century, however, according to Schmitt, this conception of politics and the State underwent a crisis with serious consequences, which lay either in the invasion of universalist tendencies undermining the special character of the State or in the subordination of politics (as the pure exercise of power) to particular interests, backroom deals, and compromises.